Synthesis, spectral and crystal structures of gem-dibromovinyl boron dipyrrins. (August 2020) - Ali, Hasrat; Guérin, Brigitte; van Lier, Johan E.
Abstract: A series of BODIPYs (boron-dipyrromethene dyes; 4, 4-difluoro-5-aryl-4-bora-3a, 4a-diaza- s -indacene) derivatives, bearing an aldehyde group at different pyrrole positions, were transformed into gem -dibromovinyl analogs using the Corey-Fuchs or Lautens olefination method. The gem -dibromovinyl moieties (one or two) are symmetric/asymmetric and attached at α- or β-positions of the pyrrole ring, directly or through the extension of a β-position substituted phenyl spacer ring. The molecular structures of the resultant dyes were assigned using MS, 1 H, 13 C, 19 F NMR, X-ray diffraction and for some compounds 2D HSQC and 11 B NMR. The absorption, fluorescence and solvatochromism properties were investigated in different solvents. The highest absorption and emission maxima were obtained for compounds having two gem -dibromovinyl groups attached directly at the α-positions. The best correlation (R-coefficient) of absorption between the solvents and spectral properties of the BODIPYs was obtained using the refractive index of the solvent. The R-coefficient of emission was obtained only for compounds having gem -dibromo vinyl moieties at α-positions. Their solid states clearly reveal distinct patterns of gem -dibromovinyl orientation, torsion angles of the 5-phenyl ring and the indacene plane. Hirshfeld surface analyses were used to visualize various intermolecular interactions. Graphical abstract: Image 1 Highlights: Asymmetric and symmetric gem -dibromovinyl BODIPY derivatives were synthesized by the Corey–Fuchs olefination method. Molecular structures were assigned using MS, 1 H, 13 C, 19 F NMR, X-ray diffraction and for some compounds 2D HSQC and 11 B NMR. Absorption, fluorescence and solvatochromism properties were investigated in different solvents. Hirshfeld surface analyses were used to visualize various intermolecular interactions. These gem-dibromovinyl derivatives can serve as building blocks for further functionalization of BODIPYs.